REBOUND: a media-based life skills and risk education programme - Jungaberle, Henrik; Nagy, Ede; Heyden, Maximilian von; DuBois, Fletcher (The Health education journal, 2015)
REBOUND is a novel media-based life skills and risk education programme developed for 14- to 25-year olds in school, university or youth group settings. This paper outlines the programme’s rationale, curriculum and implementation. It provides information of relevance to researchers, programme developers and policymakers.